2023
DOI: 10.3389/fphar.2023.1236550
|View full text |Cite
|
Sign up to set email alerts
|

A review of the pathophysiology and the role of ion channels on bronchial asthma

Indyra Alencar Duarte Figueiredo,
Sarah Rebeca Dantas Ferreira,
Jayne Muniz Fernandes
et al.

Abstract: Asthma is one of the main non-communicable chronic diseases and affects a huge portion of the population. It is a multifactorial disease, classified into several phenotypes, being the allergic the most frequent. The pathophysiological mechanism of asthma involves a Th2-type immune response, with high concentrations of allergen-specific immunoglobulin E, eosinophilia, hyperreactivity and airway remodeling. These mechanisms are orchestrated by intracellular signaling from effector cells, such as lymphocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 236 publications
0
3
0
Order By: Relevance
“…Dysfunction of CRAC channels can contribute to a myriad of diseases, including bronchial asthma [87,88], airway hyperreactivity [89], cardiovascular diseases [90][91][92], hypocalcemia [93], brain diseases [94][95][96], gastroenteric inflammation [97], as well as various carcinomas [98][99][100][101][102]. Here, we will focus on the role of ORAI in cancer.…”
Section: Orai and Cancersmentioning
confidence: 99%
“…Dysfunction of CRAC channels can contribute to a myriad of diseases, including bronchial asthma [87,88], airway hyperreactivity [89], cardiovascular diseases [90][91][92], hypocalcemia [93], brain diseases [94][95][96], gastroenteric inflammation [97], as well as various carcinomas [98][99][100][101][102]. Here, we will focus on the role of ORAI in cancer.…”
Section: Orai and Cancersmentioning
confidence: 99%
“…In addition to the CRAC channels’ role in many immune cell functions, they are also potential drug targets for the treatment of various inflammatory reactions, allergic diseases [ 118 , 119 ], and many cancer types [ 20 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ]. Several studies have confirmed that the genetic deletion or inhibition of CRAC channels hinders T cell and mast cell functions and diminishes inflammation of autoimmunity, transplant rejection, and asthma [ 119 ].…”
Section: Introduction—the Role Of Ca 2+ Release-ac...mentioning
confidence: 99%
“…In addition to the CRAC channels’ role in many immune cell functions, they are also potential drug targets for the treatment of various inflammatory reactions, allergic diseases [ 118 , 119 ], and many cancer types [ 20 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ]. Several studies have confirmed that the genetic deletion or inhibition of CRAC channels hinders T cell and mast cell functions and diminishes inflammation of autoimmunity, transplant rejection, and asthma [ 119 ]. Particularly, the development and the progression of several T cell-mediated autoimmune diseases, including inflammatory bowel disease [ 129 ] (IBD), experimental autoimmune encephalomyelitis [ 130 , 131 ] (EAE), graft-versus-host disease [ 132 , 133 ] (GvHD), and psoriasis form skin inflammation [ 134 , 135 , 136 ], have been linked to Orai and STIM proteins.…”
Section: Introduction—the Role Of Ca 2+ Release-ac...mentioning
confidence: 99%